Direct primary brown coal liquefaction via non-catalytic and catalytic co-processing with model, waste and petroleum-derived hydrogen donors. (15th December 2018) - Frątczak, Jakub; Hidalgo Herrador, José M.; Lederer, Jaromír; Stevens, Lee; Uguna, Clement; Snape, Colin; Gómez de la Fuente, José L.; Anděl, Lukáš; Svoboda, Petr; Pinto, Filomena
Abstract: Direct coal liquefaction (DCL) seems to be a suitable way to convert low rank coals into liquid fuels, especially when problematic wastes are used together with this feedstock. It is also a solution to become energy independent for many countries which have significant coal resources and limited access to crude oil. The aim of this research was to investigate DCL process by the co-processing of brown coal with model-, petroleum- and waste-derived solvents. The brown coal with and without W, Fe and Mo metals supported on its surface was tested. Thirteen DCL tests with added hydrogen pressure were carried out in the autoclave. These tests were classified in two groups. First group covered reactions using model and petroleum-derived solvents (tetralin, 1-methylnaphthalene, light cycle oil (LCO), hydrotreated LCO, C9+ fraction and decalin) with non-impregnated brown coal. Then, LCO was chosen as solvent for carrying out three tests using the metals supported on coal. Finally, waste tires pyrolysis oil was used as a waste-derived solvent for other three tests with molybdenum supported on coal. For tests using LCO, the total amount of direct liquid and n-heptane soluble products was 20 wt% higher using metal covered brown coal in comparison to unmodified one. The test with the brown coal impregnated by 1% of molybdenum resulted in the best efficiency, thus this type of coal was chosen as a catalytic feedstock for the tests with waste tires pyrolysis oil.